HSP70 induction by bleomycin metal core analogs. Issue 7 (1st April 2020) - Ali, Taha F.S.; Taira, Naomi; Iwamaru, Kana; Koga, Ryoko; Kamo, Masahiro; Radwan, Mohamed O.; Tateishi, Hiroshi; Kurosaki, Hiromasa; Abdel-Aziz, Mohamed; Abuo-Rahma, Gamal El-Din A.A.; Beshr, Eman A.M.; Otsuka, Masami; et al.
Graphical abstract: Abstract: Induction of heat shock protein 70 (HSP70) is known to be effective against various diseases. We are interested in HSP70 induction capability of an antitumor antibiotic bleomycin which produces oxidative stress by iron chelate formation and oxygen activation in a cell. The HSP70 induction activity of bleomycin and its six metal core analogs was examined, and a compound HPH-1Trt of 10 μM was found to induce this protein in a pheochromocytoma cell line and some T cell and monocytic cell lines. Its mechanism is increase of HSP70 mRNA, but higher concentration of this compound showed toxicity. Two new derivatives were then synthesized, and one of them named DHPH-1Trt was shown to have less toxicity and higher HSP70 induction activity. This study would lead to a clue for new HSP70 inducer clinically used in near future.